2016
DOI: 10.1021/acs.energyfuels.6b00238
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Changes to Low Water Content Bio-oils during Aging: An NMR, GC/MS, and LC/MS Study

Abstract: Bio-oil generated by the fast pyrolysis of biomass is an unstable material, undergoing chemical and physical transformations as the oil ages at room temperature. In this study, electrostatic precipitator (ESP) pine wood-derived bio-oil, which contains less water and does not undergo phase-separation upon aging, was characterized following accelerated aging. Bulk oil properties (percent water and viscosity) were found to increase in ways similar to conventional bio-oils. The unaged and aged bio-oil samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…This is supported by Joseph et al [1], who found catechols to have a reduced reactivity in model studies at 80°C for a period time of 40 h. A reduced activity of catechol rings can be ascribed to the lack of ring activation due to counteracting effects when two hydroxyl groups are substituted in a 1,2-pattern. Also, retene (or 7-isopropyl-1-methyl phenanthrene) was found to be relatively stable.…”
Section: Gc-ms Analysismentioning
confidence: 59%
See 3 more Smart Citations
“…This is supported by Joseph et al [1], who found catechols to have a reduced reactivity in model studies at 80°C for a period time of 40 h. A reduced activity of catechol rings can be ascribed to the lack of ring activation due to counteracting effects when two hydroxyl groups are substituted in a 1,2-pattern. Also, retene (or 7-isopropyl-1-methyl phenanthrene) was found to be relatively stable.…”
Section: Gc-ms Analysismentioning
confidence: 59%
“…The yield of insolubles in the aged LO (aLO_EIS_80) and the aged HO (aHO_TIS_80) after 1 week of ageing is 0.5 and 3.1%, respectively, showing that the ageing rate of HO is faster than that of LO at 80°C for 1 week. The formation rate of insolubles (aLO_EIS_80 and aHO_TIS_80) in this study is relatively low compared to the biomass-pyrolysis bio-oil [1,7,[13][14][15]. The LO and HO produced by the HTL of lignin have, thus, a comparably high degree of stability at 80°C.…”
Section: Fractionation and Yields Of The Bio-oilmentioning
confidence: 75%
See 2 more Smart Citations
“…17,18 Furthermore, the phase stability of FP bio-oils has recently been reviewed. 19 The chemical composition of aged biooils has been reported, [20][21][22][23][24][25] and other advanced characterizations have been performed. 26 It has also been shown that bio-oil aging is an exothermic process.…”
Section: Introductionmentioning
confidence: 99%